EKSPLORASI ETNOMATEMATIKA PADA PENERAPAN KONSEP PERBANDINGAN DALAM PEMBUATAN LEPET KETAN - Mufida, Sayidatul; Wildan, Hakim (FKIP Universitas Mataram, 2025)
Ethno-mathematics is a field of study that connects mathematical concepts with people's cultural practices. This study aims to examine the application of ethno-mathematics in the process of making lepet ketan, a traditional Indonesian food made from sticky rice wrapped in janur. Lepet ketan not only has culinary value, but also reflects local wisdom in processing natural ingredients. In this study, we analyzed the various stages of making lepet ketan and found that many mathematical concepts, especially comparison and measurement, are involved in the process. Artisans must determine the right ratio between sticky rice, grated coconut and tolo nuts to achieve a balanced flavor. The methods used include direct observation and interviews with glutinous rice lepet artisans in Tawangrejeni Village. The research findings show that people intuitively apply mathematical principles in their daily lives, especially in the process of traditional food making and marketing. The craftsmen also have to consider the size of the janur as well as the amount of ingredients needed, all of which involve comparison and measurement. The patterns that emerge in the preparation of lepet ketan reflect regularities that can be analyzed mathematically. This research confirms the importance of ethno-mathematics as a bridge between culture and mathematics education. By integrating mathematical concepts in the cultural context of lepet ketan, we can create a bridge between culture and mathematics education. Keywords: sticky rice ; ethnomathematics ; and comparison